Retrospective Results of Malignant Glioma Patients Receiving Primary and/or Postoperative Radiotherapy and Comparison with Different Prognostic Indices - ATASOY, BESTE MELEK; ALSAN ÇETİN, İLKNUR (ORTADOGU AD PRES & PUBL CO, 2012)
Objective: This study aimed to retrospectively evaluate malignant glioma (MG) patients and compare the prognostic factors with different indices. Material and Methods: A total of 204 patients diagnosed as malignant glioma and received primary and/or postoperative radiotherapy (RT) were retrospectively evaluated. Median follow up was nine months (1-90), median survival was 10 months, one-year survival rate was 42%. Of the patients, 16% had grade III anaplastic astrocytoma, 84% had grade IV glioblastoma multiforme. While surgical operation was limited with stereotactic biopsy in 59 (29%) patients, 59 (29%) underwent subtotal and 86 (42%) underwent gross total resection. Prognostic factors affecting survival were tested with univariate and multivariate analyses. Results: In univariate analysis, histology, age, preRT Karnofsky performance status (KPS), preoperative KPS, onset time of symptoms, history of seizures, tumor's not being multicentric, complete surgical resection and RT dose were found to be the factors affecting survival. In multivariate analysis, histology, age, onset time of symptoms, surgery type and RT dose were detected as independent prognostic factors. When the data of our patients were classified according to Radiation Therapy Oncology Group Recursive Partitioning Analysis classification, the survival was 70,13,11,8, 3 months for groups 1 and 3-6, respectively; it was 24, 13, 9, 8 and 4 months for groups 1-5, respectively according to Medical Research Council prognostic index; and 13, 7 and 5 months for groups 1-3, respectively according to Dokuz Eylul University prognostic index (long rank test p<0.0001). Conclusion: As treatment options, contribution of surgery and/or radiotherapy to survival is limited when applied to patients diagnosed with malignant glioma. Additional treatment modalities are needed in addition to these treatment modalities. Prognostic classifications should be used for determination of the treatment.
Keywords: Glioma; mortality; THERAPY-ONCOLOGY-GROUP; RECURSIVE PARTITIONING ANALYSIS; MEDICAL-RESEARCH-COUNCIL; GLIOBLASTOMA-MULTIFORME; RANDOMIZED-TRIAL; ASTROCYTOMA; SURVIVAL; TEMOZOLOMIDE; VINCRISTINE; VALIDATION